Cultivating Flexible Working Through Dynamic Working Arrangement for Public Organization in West Java - Amanda, Dadan; Rahman, Abdul; Pradesa, Hafid Aditya (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2025)
The COVID-19 pandemic has accelerated the adoption of flexible work policies in the public sector, including at the Regional Secretariat of West Java Province. One such initiative, the Dynamic Working Arrangement (Mekanisme Kerja Dinamis or MKD), is crucial for integrating technology and talent management to make the bureaucracy more agile and responsive to change. This study analyzes the implementation of MKD, identifies its challenges, and proposes an ideal development model. To achieve these goals, the research employs a descriptive qualitative method based on policy implementation theory, focusing on an analysis of both policy content and its implementation context. The research process begins with data collection through interviews, observations, and document analysis, with the validity and reliability of the data later being verified through triangulation. The findings indicate that while MKD effectively enhances work efficiency and flexibility, significant barriers persist, such as resistance to work culture change, uneven workload distribution, and limited technological infrastructure. Based on these findings, recommendations for improving MKD include strengthening internal communication, enhancing the digital competencies of civil servants, and reforming performance management systems. With these advancements, MKD is expected to evolve into a more effective and sustainable flexible work model.